Waste machines as an alternative way to enhance students’ speaking interest - Yuliana Ningsih; Kurnia Dwi Artika (UAD TEFL International Conference)
The phenomenon this time was that many lecturers had fallen asleep with the technological advancements used in the learning media. By relying on a more unique creativity, this study used simple materials from spare parts of a machine that can be used as learning media especially in speaking interest. The paper aims to explore speaking interest through waste machines to the students of Mechanical Engineering, the State Polytechnic of Tanah Laut. It investigates how waste machines can be incorporated in English for Specific Purpose (ESP) learners’ speaking interest. This study was qualitative case study, and data were gathered through observations, field notes and interviews. Data were interpreted based on the prepared achievements indicator. The results of the study reveal that the utilization of waste machines such as shocks, piston, gear, and bold is successful improving speaking skill for the students of Mechanical Engineering. In addition, students also learnt how to deliver in presentation with their field studies.